Preeclampsia and eclampsia complicated with retinal detachment. Report of three cases - Turcios, Francisco Eduardo (2023)
Preeclampsia is a multisystemic hypertensive disorder that occurs after 20 weeks ofgestation in 5%-15% of pregnant women and is the cause of complications that canaffect important organs and even cause death during gestation or in the postpartumperiod. It includes severe preeclampsia, eclampsia and HELLP (hemolysis, elevationof liver enzymes, low platelets) syndrome. We report three cases of retinaldetachment that occurred in two patients with severe preeclampsia and one witheclampsia, all with hemorrhage and visual alteration in the postpartum period thatrequired pharmacological treatment. Retinal detachment is a symptom associatedwith preeclampsia and eclampsia that can be investigated by ocular fundoscopy todetermine whether conservative or pharmacological treatment is feasible.